Interpreting the Budgeting Process of Social and Environmental Responsibility at PT Kaltim Industrial Estate Title - Hartono, Yudi; Kusumawardhani, Anisa; Bone, Hariman (International Forum of Researchers and Lecturers, 2025)
This study aims to interpret the budgeting process in the policy-making of Social and Environmental Responsibility (TJSL) at PT Kaltim Industrial Estate (KIE). Using a qualitative-interpretive approach through a single instrumental case study, data were collected from interviews with key informants, observations, and document analysis. The findings reveal that TJSL budgeting at KIE is not merely a technical process but rather a complex arena of meaning negotiation. This process reflects the company’s efforts to respond to institutional pressures while simultaneously building social legitimacy. Five main themes were identified: (1) the interpretation of TJSL as a commitment to sustainability and Creating Shared Value (CSV); (2) the integration of TJSL into corporate strategy; (3) a bottom-up and participatory budgeting process; (4) priority setting influenced by institutional pressures and financial capacity; and (5) program evaluation involving external parties. The study concludes that the interpretation of TJSL has shifted from a symbolic obligation to a strategic investment, substantively integrated into corporate governance to ensure business sustainability.